POLA HUBUNGAN PATRON-KLIEN DAN PERANNYA DALAM PEMBENTUKKAN KAPITAL SOSIAL DAN KAPITAL DIGITAL PETANI - Rivanisa, Firdarani Kirana (Istek Widuri Jakarta, 2022)
A patron-client relationship is a dyadic relationship that is often found in most agrarian settings in Indonesia. The patron-client relationship that manifests is usually comprised of exploitative and repressive actions. Patrons are often assumed as actors who perpetuate peasant poverty. Even so, patrons have higher socioeconomic status and resources that can be transferred and beneficial to their clients. This paper aims to describe the pattern of patron-client manifested in the relationship between patrons and farmers in Desa Tani Mandiri Program and its role in the formation of social capital and digital capital. This study uses a qualitative approach and a descriptive method. The results of this study indicate that the patron-client relationship that exists is formed because of social inequality that forces patrons and clients to associate with each other for profit. Another forming element is the existence of personal relationships and the flexibility that both offers. Reciprocity between patrons and clients is quite balanced due to the existence of social capital and digital capital, promoted by the patron-client relationship itself. With the formation of social capital and digital capital, clients have more bargaining power and have the ability to reduce their level of dependence on the patron.